(untitled) (Czech Journal of Multidisciplinary Innovations, 2023)
This article explores the evolving landscape of investor-state arbitration (ISA) in the context of shifting geopolitical dynamics and changing global economic powers. As the world undergoes significant transformations in its political and economic spheres, the traditional framework of ISA faces unprecedented challenges. This study employs a comprehensive analysis to investigate the future prospects of ISA, considering the influence of emerging economic superpowers and their impact on the international investment regime. The findings suggest that ISA is at a crossroads, demanding innovative reforms and adaptability to maintain its relevance in the rapidly changing world order.